2003
DOI: 10.1073/pnas.0337563100
|View full text |Cite
|
Sign up to set email alerts
|

Direct detection of antibody–antigen binding using an on-chip artificial pore

Abstract: We demonstrate a rapid and highly sensitive all-electronic technique based on the resistive pulse method of particle sizing with a pore to detect the binding of unlabeled antibodies to the surface of latex colloids. Here, we use an on-chip pore to sense colloids derivatized with streptavidin and measure accurately their diameter increase on specific binding to several different types of antibodies. We show the sensitivity of this technique to the concentration of free antibody and that it can be used to perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
128
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(133 citation statements)
references
References 31 publications
2
128
0
Order By: Relevance
“…The fully electrical molecular detection is also unique compared with technologies such as Biacore, a surface plasmon resonancebased bioanalyzer (28), in that it works without optical signal readout. For such electrical detection, a nanoporous structure is known to be suitable, especially when it is used in resistive-pulse mode (29,30). In this study we showed another practical option using functionalized glass nanopipettes in which antibodies of interest were immobilized on the surface of individual nanopipettes rather than dispersed in the bulk solution.…”
Section: Discussionmentioning
confidence: 96%
“…The fully electrical molecular detection is also unique compared with technologies such as Biacore, a surface plasmon resonancebased bioanalyzer (28), in that it works without optical signal readout. For such electrical detection, a nanoporous structure is known to be suitable, especially when it is used in resistive-pulse mode (29,30). In this study we showed another practical option using functionalized glass nanopipettes in which antibodies of interest were immobilized on the surface of individual nanopipettes rather than dispersed in the bulk solution.…”
Section: Discussionmentioning
confidence: 96%
“…It is a classic flow cytometer based on the electronic detection method that employs the modulation of electrical resistance in an electrical ion current for label-free biological sample identification and analysis. Resistive pulse sensing method has been widely applied for sensing microparticles, such as polystyrene particles (Xu et al 2007), single DNA molecules (Saleh and Sohn 2003a), proteins (Wharton et al 2007), antigen and antibody (Saleh and Sohn 2003b;Carbonaro and Sohn 2005). The sensitivity of resistive pulse approach depends on the volume ratio of the sample and has a much lower manufacturing and operational cost.…”
Section: Introductionmentioning
confidence: 99%
“…1 The immunoassay is an antibody-based detecting technique for a specific antigen; 2 it exploits highly sensitive and specific binding interactions between an antigen and an antibody. 3,4 Depending on the assay format, immunoassays can be used qualitatively and quantitatively, and the application of immunoassays has been extended to various research fields, such as environmental monitoring, medical diagnostics, proteomics, pharmaceutical drug screening research, and basic cellular analytical research. 5,6 Enzyme-linked immunosorbent assays (ELISAs) are the most fundamental and basic immunoassay for clinical diagnostic and biological research fields, due to their high sensitivity and versatility.…”
Section: Introductionmentioning
confidence: 99%